Roosting behaviour and site mapping of cave dwelling bats in wind cave nature reserve, Bau, Sarawak, Malaysian Borneo - Qhairil Shyamri, Rosli; Faisal Ali, Anwarali Khan; Muhd Amsyari, Morni; Julius Willian, Dee; Roberta Chaya, Tawie Tingga; Mohd Ridwan, Abd Rahman (Malaysian Society of Applied Biology, 2018)
A roost survey of cave-dwelling bats in Wind Cave Nature Reserve (Wind Cave NR) was conducted for 11 days from July 2013 until April 2014. This study aims to explore roosting ecology of bats in Wind Cave NR. From the total of 462 observations, five families of bats were recorded comprising 11 species of bats. These species include Penthetor lucasi, Megaderma spasma, Myotis horsfieldii, Rhinolophus affinis, R. borneensis, Hipposideros ater, H. cervinus, H. coxi, H. diadema, H. galeritus and H. larvatus. Penthetor lucasi was the most abundant species observed with colony size >100 individuals. Whereas the most roost observations was set by M. horsfieldii with 136 observations and the most diverse family was set by Hipposideridae with six species. Chi square analyses using contingency table showed statistically significant association existed between roost behaviour and the bats assemblages (p<0.05). Another key finding in this study is the discovery of a colony of H. coxi, a Bornean endemic species that serve as the first ever record for this species inside a cave and for Wind Cave NR. Overall information presented herein able to assist the local management in developing strategy for conservation, long-term species monitoring and beneficial in ecotourism purposes.